The Relationship Between Learning Motivation And Learning Difficulties Of Cashity At Modeste Dolly Women's Skill Institution, Bukittinggi City - Elsa Mayori; Wirdatul 'Aini Wirdatul 'Aini (Universitas Negeri Padang, 2023)
The background of this research is the high learning difficulty of dressmaking students at the Modeste Dolly Women's Skills Institute, which is suspected to be due to the low learning motivation of students at the Modeste Dolly Women's Skills Institute, Bukittinggi City. This study aims to reveal an overview of the learning motivation of fashion design students, learning difficulties of fashion design students, and reveal the relationship between learning motivation and learning difficulties of fashion at the Modeste Dolly Women's Skills Institute, Bukittinggi City. This study uses a quantitative approach with a correlational type. The population in this study were 45 fashion students, while the samples were taken using a 70% stratified random sampling technique, namely 32 people. Data collection techniques using a questionnaire. And the technique used in data analysis is the percentage formula and product moment correlation formula. The results of this study indicate that: 1) the learning motivation of dressmaking students is still relatively low; 2) the learning difficulties of dressmaking students are high; 3) there is a significant relationship between learning motivation and learning difficulties in fashion at the Modeste Dolly Women's Skills Institute Bukittinggi City.